Representations of religious identity in the novels of Mohamed Sari - Mehdi, Salah Eddine (El Omda in Linguistics and Discourse Analysis, 2025)
This research study addresses the manifestations and manifestations of religious identity, represented by evoking the Holy Qur’an and Quranic stories, as well as the noble Prophetic hadiths and the biography in the fictional work of the great novelist Muhammad Sarim . Sari's narrative text is filled with several religious evidences that prove the extent of the identity and originality of the writer, and behind him, Algerian society throughout different historical periods. Like the revolution, the colonial period, and the years of blood and fire (the Black Decade), the writer’s religious absorption contributed to demonstrating the strength and closeness of the relationship that links Algerian society with the Islamic religion, and that it constitutes the core of its identity and its backbone.